2020
DOI: 10.1021/acsphotonics.0c00064
|View full text |Cite
|
Sign up to set email alerts
|

Spin Angular Momentum of Guided Light Induced by Transverse Confinement and Intrinsic Helicity

Abstract: In recent years, extraordinary spin angular momenta have been investigated in a variety of structured electromagnetic waves, being of especial interest in sub-wavelength evanescent fields. Here we demonstrate analytically that, in planar and cylindrical waveguides supporting transverse electric/magnetic modes, transverse spin density arises inside the waveguide (different from the spin induced in the evanescent region outside the waveguide), carrying indeed longitudinal extraordinary (so-called) Belinfante's s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 70 publications
0
27
0
1
Order By: Relevance
“…On the other hand, for cylindrically symmetric particles, the absence of backscattered light follows from the preservation of EM helicity [14][15][16][17][18]. Conservation of helicity has proven crucial in many applications such as enhanced chiral light-matter interactions [19][20][21][22][23][24][25], or in the spin-orbit interactions of light [26][27][28][29][30][31][32]. In this vein, it has been reported that from a relatively simple far-field measurement of the EM helicity at a right angle, the radiation pattern of the dipolar particle is inferable [33].…”
mentioning
confidence: 99%
“…On the other hand, for cylindrically symmetric particles, the absence of backscattered light follows from the preservation of EM helicity [14][15][16][17][18]. Conservation of helicity has proven crucial in many applications such as enhanced chiral light-matter interactions [19][20][21][22][23][24][25], or in the spin-orbit interactions of light [26][27][28][29][30][31][32]. In this vein, it has been reported that from a relatively simple far-field measurement of the EM helicity at a right angle, the radiation pattern of the dipolar particle is inferable [33].…”
mentioning
confidence: 99%
“…Moreover, by choosing a square cross section, we ensure that the two first guided modes (i.e., the TE and TM modes) appear to be degenerate. Unlike wires with circular cross section, [48][49][50] there is no analytical solution for the propagating modes of square (or, in general, rectangular) dielectric waveguides, so we ought to calculate the corresponding guided modes by means of numerical simulations. This has been performed with the aid of the commercial 3D full-wave solver CST Microwave Studio (Section 6).…”
Section: Optical Chirality Density In All-dielectric Integrated Photomentioning
confidence: 99%
“…In this regard, it should be noted that, apart from the case of plane-wave propagating in free space, studies on optical chirality (and/or helicity [8] ) in integrated platforms are scarce, with the notable exception of cylindrical dielectric waveguides, for which there are analytical solutions. [48][49][50] In this work, we investigate the existence of (enhanced) optical chirality in lithographically defined integrated dielectric waveguides, as well as its potential in chiral applications such as sensing or spectroscopy. In particular we focus on two of the most common guiding structures used in nanophotonics: strip and slot waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, coupling of the light to the resonant modes of the nanostructure 1 , 2 can tailor the light absorption 3 5 , reflection 6 , emission 7 9 and lasing 10 , 11 , important for both photodetector and source applications. Furthermore, evanescent modal fields in semiconductor NWs have been shown to carry transverse spin angular momentum (SAM) 12 , 13 , therefore it came naturally to extend NW investigation to spin-related phenomena, chirality and circular dichroism (CD) i.e. different interaction with circular polarizations (CP) of opposite handedness.…”
Section: Introductionmentioning
confidence: 99%